Resíduos de serviços de saúde: programa de educação continuada para os servidores do laboratório de análises clínicas do Hospital Universitário de Santa Maria - Santos, Silvia Donizete (2014)
The residues from wealth service require a differentiated treatment due to its high contamination and accident risks. The wealth professions need knowledge about the way to segregate, treat and give an adequate destiny for residuals from their activity. So, organizations in this area should adopt procedures established by law, by empowerment and continuous education for the multivariate staff in relation to the management of wealth service residuals (RSS). The objective of this study was to suggest a continuous education programme for medical laboratory employees from University Hospital of Santa Maria (LAC/HUSM) in relation to residual generated. This study is justified by the increasing rigour in legislation referred to wealth and environmental areas related to RSS management, and the lack of a continuous education programme for LAC/HUSM staff. A qualitative and exploratory approach has been chosen to develop the investigation. A case study method has been used. The data has been collected by the consultation of documents in the archives, observation in a laboratory considered a reference and interviews. The subjects of study have been employees hired by the Single Legal System who work at LAC/HUSM. To analyze the information, the technique of data triangulation has been used, as well as software NVivo. Results emphasize that the continuous education programme proposed lasts 15 hours and is formed by three steps, and the main subjects are: RSS legislation and its applications at LAC/HUSM; RSS of LAC/HUSM and biosafety; and also knowing the main paths of RSS from LAC/HUSM.